Cholecystectomy and the development of colorectal neoplasia: a prospective study. - Moorehead, R. J. (Royal College of Surgeons of England, 1989)
One hundred asymptomatic patients over 60 years of age who had cholecystectomy carried out at least 10 years earlier underwent double contrast barium enema and sigmoidoscopy. The incidence of colorectal adenomas and carcinomas was compared with age and sex matched controls undergoing routine post mortems. In the post-cholecystectomy group 12% had tumours (8 adenomas greater than 1 cm in diameter, 4 carcinomas). In the control group 3% had tumours (3 adenomas); P = 0.02. This study confirms that patients with a history of cholecystectomy have an increased risk of developing colorectal adenomas and carcinomas.